Advances in invertebrate (neuro)endocrinology : a collection of reviews in the post-genomic era. Volume 1, Phyla other than anthropoda - Saleuddin, Saber; Lange, Angela, 1957-; Orchard, Ian, 1951- ([Oakville, ON] : Apple Academic Press, 2020)
Advances in Invertebrate (Neuro)Endocrinology: A Collection of Reviews in the Post-Genomic Era (2-volume set) provides an informative series of reviews from expert scientists who are at the forefront of their research into the endocrinology of invertebrates. These two volumes are timely and appropriate in this post-genomic era because of the rapid pace of change brought about by genome projects, functional genomics, and genetics (omics technologies). The volume shows the rich history and strong tradition of cutting-edge research using invertebrates that has opened up our broader understanding of comparative endocrinology and the evolution of regulatory pathways and systems. These reviews set the scene and context for this exciting new era of understanding that has come from this post-genomic revolution.
OCLC-licensed vendor bibliographic record.
Keywords: Invertebrates -- Endocrinology; Arthropoda; Phyla (Genus); Endocrinology, Comparative